Case–Control and Family‐Based Association Study of Specific PTPRD Variants in Restless Legs Syndrome. Issue 5 (9th January 2016) - Gan‐Or, Ziv; Zhou, Sirui; Johnson, Amelie; Montplaisir, Jacques Y.; Allen, Richard P.; Earley, Christopher J.; Desautels, Alex; Dion, Patrick A.; Xiong, Lan; Rouleau, Guy A.
Abstract: Background: The exact genetic causes within each of the known restless legs syndrome (RLS) loci are still unknown. Recently, it was suggested that an intronic protein tyrosine phosphatase, receptor type δ ( PTPRD ) single‐nucleotide polymorphism (SNP) (reference SNP no. rs2381970) is associated with its expression, which may lead to RLS and other related phenotypes. Another study identified 3 nonsynonymous PTPRD variants in familial RLS cases: p.Q447E (a residue change from glutamine to glutamic acid at position 447), p.T781A (a residue change from threonine to alanine at position 781), and p.R995C (a residue change from arginine to cysteine at position 995). Methods: Two cohorts of sporadic RLS, a French‐Canadian cohort and a cohort from the United States, with a total of 577 patients and 455 controls, and an additional familial RLS cohort with a total of 635 individuals (140 families) were genotyped for these 4 variants (rs2381970, p.Q447E, p.T781A, and p.R995C) by using specific TaqMan probes, and the effects of each variant as well as haplotypes were analyzed. Results: None of the 4 PTPRD ‐specific variants or haplotypes that were tested were associated with RLS in the case–control cohorts or in the familial cohort. The frequencies of the rs2381970 variant in the French‐Canadian and US cohorts were 0.07 and 0.04, respectively, and their frequencies in the respective control populations were 0.06 and 0.04, respectively ( P > 0.4 for both). Similar results were obtained for the 3 nonsynonymous variants. Conclusions: Although the PTPRD gene is well established as an RLS‐associated locus, the rs2381970 SNP and the 3 nonsynonymous PTPRD variants are not likely to cause or affect the risk for developing RLS in the study population. More studies in other populations are needed to determine their potential role in RLS.